THE ROLE OF PARENTS EDUCATION TOWARDS CHILDREN IN REMEMBERING THE PROHIBITION TO LIKE FELLOW GENDRE (Case study of Al-Qur'an Surah An-Nahl Verse 72) - Latifudin Al-islamy (Almarhalah, 2023)
The role of parental education for children is very important for the growth and development of children. Moreover, it refers to the demands of a child's social life, the child must be able to sort and judge which one is good and which one is bad to do, this refers to a child's education system that affects a child's development process in assessing what is good for him/her and which is bad for him. So here is how important the role of parental education for children is in understanding how important it is to educate children to stay away from deviant actions. This can be seen from how parents remind their children not to do things that deviate from the teachings of Allah SWT. This research methodology uses qualitative methods (qualitative research). The data refers to a case study, namely the Al-Qur'an Surah An-Nahl Verse 72, where in this verse it will become a valid source of data to be described and made into good writing in this paper.